Alloreactive-free CAR-VST therapy: a step forward in long-term tumor control in viral context - Wang, Valentine; Savoldo, Barbara; Guimaraes, José-Arthur; Dotti, Gianpietro; Reppel, Loïc; Bensoussan, Danièle (Frontiers in Immunology, 2025)
CAR-T cell therapy has revolutionized immunotherapy but its allogeneic application, using various strategies, faces significant challenges including graft-versus-host disease and graft rejection. Recent advances using Virus Specific T cells to generate CAR-VST have demonstrated potential for enhanced persistence and antitumor efficacy, positioning CAR-VSTs as a promising alternative to conventional CAR-T cells in an allogeneic setting. This review provides a comprehensive overview of CAR-VST development, emphasizing strategies to mitigate immunogenicity, such as using a specialized TCR, and approaches to improve therapeutic persistence against host immune responses. In this review, we discuss the production methods of CAR-VSTs and explore optimization strategies to enhance their functionality, activation profiles, memory persistence, and exhaustion resistance. Emphasis is placed on their unique dual specificity for both antitumor and antiviral responses, along with an in-depth examination of preclinical and clinical outcomes. We highlight how these advances contribute to the efficacy and durability of CAR-VSTs in therapeutic settings, offering new perspectives for broad clinical applications. By focusing on the key mechanisms that enable CAR-VSTs to address autologous CAR-T cell challenges, this review highlights their potential as a promising strategy for developing effective allogeneic CAR-T therapies.